Islamization in South Sulawesi and Its Institutionalisation As The State Religion (1605–1611) - Nasihin, Nasihin; Junaeda, St.; Tajuddin, Fatjri Nur (Universitas Islam Negeri Madura, 2024)
This paper explains how changing Islam, previously the religion of the people of South Sulawesi, became the state religion (Gowa-Tallok Kingdom). Placing the right context in institutionalizing Islam in the Gowa-Tallok Kingdom can explain how Islamization in South Sulawesi took place until 1611. The historical method is used, which focuses on the causal aspects of the events being studied. The causal aspect of events is based on the narrative contained in the sources and references referred to as a marker of library research. This paper explains that the conversion of Islam in South Sulawesi society occurred long before Islam became the state religion. Adaptively, the people of South Sulawesi have been exposed to Islam through a network of Muslim traders and muballigh for 125 years. The people of South Sulawesi had been familiar with the teachings of Islam, subject to external pressures that favored the conversion of local religions to Islam. When Islam was institutionalized as the state religion, it took only 7 (seven) years to convert the people of South Sulawesi to Islam. By 1611, South Sulawesi had been Islamized, except for the mountainous areas in the north.